Integrative Management of Amavata (Rheumatoid Arthritis): A Case Study Highlighting Ayurvedic Interventions for Detoxification and Digestive Support - Shetti, Uma; Reddy, Jeeru Ojaswini; Killedar, Ramesh Shivappa; Hegade, Prabhakar (Asian Journal of Biological and Life Sciences, 2025)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune disease-causing joint inflammation, pain, swelling, and stiffness. Conventional treatments, including DMARDs and biologics, often provide incomplete relief, leading patients to explore Ayurveda. In Ayurveda, RA is correlated with Amavāta, resulting from Ama (toxins) accumulation and Vata imbalance. A 56-year-old woman with chronic RA symptoms sought Ayurvedic treatment after partial relief from conventional therapy. She presented with persistent joint pain, stiffness, and elevated inflammatory markers, including rheumatoid factor, C-Reactive Protein (CRP), and Erythrocyte Sedimentation Rate (ESR). Objectives: Ayurveda management of Amavata through Nitya Virechana, Vāluka Sweda, Dhānyakādi Siddha Jala, and oral formulations. Materials and Methods: This prospective case study examined a diagnosed Rheumatoid Arthritis (RA) patient undergoing a three-month Ayurvedic treatment. The protocol included Nitya Virechana and Vāluka Sweda for the initial seven days, followed by the oral administration of Simhanada Guggulu and Rasna Saptaka Kashaya for three months. Additionally, Dhānyakādi Siddha Jala, prepared with Dhānyaka, Śuṇṭhī, and Jīraka, was administered. The patient's progress was assessed every 30 days over three months, with treatment efficacy evaluated based on clinical symptom reduction, improvement in the Visual Analog Scale (VAS) score, and post-treatment blood test results. Results: The patient experienced gradual symptom relief throughout the treatment. By the end, blood tests showed significant improvement, with reduced symptoms and enhanced overall health and quality of life. Conclusion: This case study suggests that an Ayurveda treatment protocol incorporating Nitya Virechana, Vāluka Sweda, oral medications, and Dhānyakādi Siddha Jala may be beneficial in the management of Amavāta (Rheumatoid Arthritis).
Keywords: Amavata; Bruhat saindavadi taila; Dhanyakadi sidda jala; Nitya Virechana